Global Perspectives on Underutilized Crops (Springer International Publishing, 2018)
Increase in world population, extreme weather conditions, decrease in fresh water supplies, and changes of dietary habits are major issues that affect global food security. We are expected to face the challenges of land use by 2050 because population will reach 9 billion while agricultural productivity losses are expected due to overuse of lands. How can we feed the next generations in a manner that respects our finite natural resources? Managing our resources in a sustainable way have only begun for selected crops. Much remains to be done to increase food yield. Cropping practices capable of sustainable production need to be elaborated, especially in fragile ecosystems. Typical applications will include the improvement and use of genetic resources; crop management and diversification; diffusion of improved varieties; development of cropping systems; sustainable cropping systems for areas prone to environmental degradation; use of agro-ecological data for crop production forecasting; and networks for regional coordination, and data exchange. The impetus behind this book is to bring attention to a cropping system that bear direct relevance to sustainable agriculture and food security. "Underutilized" crops are found in numerous agricultural ecosystems and often survive mainly in marginal areas. It is timely to review their status because, in recent decades, scientific and economic interests have emerged which focus on lesser-known cultivated species. Underutilized crops have a great potential to alleviate hunger directly, through increasing food production in challenging environments where major crops are severely limited. "Global Perspectives on Underutilized Crops" is therefore topical and highlights the unmet agricultural challenges that we face today. This book is an important resource for students and researchers of crop science and agricultural policy makers.